Vessels - McLerran, Jennifer, author; Yust, Dave, 1939-, advisor; Dietemann, David L., committee member; Berland, John C., committee member (Colorado State University. Libraries, 1989)
My artwork serves as a means of exploration of ideas and of representations of experience. I choose to deal with symbols because, as carriers of meaning in the context of various cultures, symbols afford an exploration of the varied ways in which meaning is made. Use of symbols from diverse cultures allows me to comparatively examine the systems of thought from which such images arise. I intend to make no definite assertion in my work regarding the nature of symbol systems or of the meanings conveyed through such symbols. I only intend tentative explorations. The lack of definite assertion in my work is appropriate to its thematic concerns -- symbols of birth, images of time's passage and its manifestation in the process of aging, and conceptions of death and an afterlife -- since any understanding of these aspects of experience must ultimately remain tentative. I aim to express a sense of this mystery in my work, but to do so with a sense of irony.
Keywords: Symbolism in art